Safety and efficacy of outpatient intravenous diuresis in decompensated heart failure: a systematic review - Kalkur, Roshni S.; Hintz, John P.; Pathangey, Girish; Manning, Katharine A. (Frontiers in Cardiovascular Medicine, 2024)
IntroductionHeart failure (HF) burdens the US healthcare system, with annual costs exceeding $30 billion. Outpatient intravenous (OP IV) diuresis in clinic or home settings may potentially improve outcomes and reduce costs, though limited data exists. This systematic review evaluates the safety, efficacy, and outcomes of OP IV diuresis in managing decompensated HF as a hospitalization alternative.MethodsFollowing PRISMA 2020 guidelines, this systematic review used MeSH terms in MEDLINE, SCOPUS, CINAHL Complete, and Cochrane Central. From 16 selected studies, 15 were single-center; 6 prospective, 9 retrospective; and 1 was a randomized trial comparing OP IV diuresis to oral home regimen. Demographics, visit data, and outcomes were collected, and 30-day outcomes were compared to inpatient IV (IP IV) diuresis from 2021 Medicare HF hospitalizations.ResultsThe review included 1,590 unique patients treated with OP IV diuretics, with a mean age of 70 ± 6 years, 69.7% male, and 74.8% NYHA III-IV. Minimal adverse post-diuresis events such as hypokalemia, hypotension, and worsening renal function occurred (4.5%, 0.7%, and 2.3% respectively). Post-visit mean weight loss was −2.2 ± 1.1 kg. The 30-day readmission rate for OP IV diuresis was significantly lower than IP IV diuresis (20.0% vs. 22.6%; p = 0.0.401), and 30-day mortality was also lower (5.6% vs. 10.7%; p = 0.003).DiscussionOP IV diuresis is a safe and effective treatment for decompensated HF with minimal risk of adverse events. Data demonstrate reduced 30-day readmission, mortality rates, cost. These findings highlight the potential of OP IV diuresis as an enhanced alternative HF care; however, further randomized control trials are needed to evaluate long-term outcomes.